2021
DOI: 10.2147/ott.s254167
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Crocin Against Gastric Carcinoma via Regulating TPM4 Gene

Abstract: Background: Gastric cancer (GC) is one of the most common malignant tumors and the second most frequent cause of cancer death worldwide. Crocin is a kind of bioactive constituent found in the stigmas of saffron, which has shown various pharmacological activities. Methods: In this study, we investigated the inhibitory effect of crocin on gastric cancer AGS cells proliferation and explored the underlying mechanism. A series of methods were used including cell counting kit assay, gene microarray analysis, qRT-PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The data showed the mRNA ( Figure 11A ) and protein expression ( Figure 11B ) levels of TPM4. In our previous study, after shRNA lentivirus infection, the knockdown efficiency of shTPM4 was 71.1%, and the knockdown of TPM4 inhibited GC cell proliferation ( 15 ) ( Supplementary Figure 2 ). In this research, wound healing and transwell assays were used to determine the migration potential of GC cells.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The data showed the mRNA ( Figure 11A ) and protein expression ( Figure 11B ) levels of TPM4. In our previous study, after shRNA lentivirus infection, the knockdown efficiency of shTPM4 was 71.1%, and the knockdown of TPM4 inhibited GC cell proliferation ( 15 ) ( Supplementary Figure 2 ). In this research, wound healing and transwell assays were used to determine the migration potential of GC cells.…”
Section: Resultsmentioning
confidence: 90%
“…In our previous study, TPM4 was found to function as an oncogene that stimulates the proliferation of cells and prevents the death of cells by apoptosis both in vitro and in vivo . TPM4 was found to be expressed at higher levels in GC tissues than in paracancerous tissues ( 15 ). However, comprehensive studies on the relevance of TPM4 expression in tumor immune cell infiltration, ICP gene expression, TMB, MSI, NEO, ceRNA, drug sensitivity, and the pan-cancer mechanism of action of TPM4, especially in GC, have seldom been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…A latest research by Xia et al [23] , demonstrated that overexpression of SLC7A2 suppressed the invasion and metastasis of hepatocellular carcinoma by regulating myeloid-derived suppressors cell recruitment. However, increased ELMO2 [24] and TPM4 [25] were related to the proliferation and metastasis of different cancers respectively, suggesting that they might contributed little to the regulation of miR-451 on RF/6A cell proliferation. RIC8A, was involved in the regulation of cell adhesion and migration.…”
Section: Discussionmentioning
confidence: 97%
“…Proteins encoded by CFL1, S100A6, ACTB, VIM, PFN1, ANXA2, RAN , and TPM4 have been found to be involved in the transport of actin–cofilin complex from the cytoplasm to nucleus, cell cycle process and differentiation, cell structure integrity and intercellular signal transfer, cytoskeleton stabilization and cytoplasmic integrity, regulation of cell growth, control of DNA synthesis, and regulation of microtubule polymerization during mitosis. All of these factors are critical in cell proliferation and differentiation (Filipek & Leśniak, 2020; Gibbs et al, 2019; Guo et al, 2013; Huang et al, 2020; Luo et al, 2021; Song et al, 2020; Wachsmannova et al, 2019; Z. L. Yang et al, 2013; C. Zhang et al, 2020). At the same time, the KEGG signal route was shown to be engaged in the Rap1 signal pathway, the Hippo signal pathway, focal adhesion, and other molecular signal pathways, all of which are significant in the activity of ADSCs stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, pseudo-time may be used to examine cell subsets or key genes of important differentiation nodes in the process of cell differentiation or development. This approach is now widely used to recreate the developmental pathway and differentiation (Filipek & Leśniak, 2020;Gibbs et al, 2019;Guo et al, 2013;Huang et al, 2020;Luo et al, 2021;Song et al, 2020;Wachsmannova et al, 2019;Z. L. Yang et al, 2013;C.…”
Section: Gene Expression Features Of Stemness In Distinct Adscs Clustersmentioning
confidence: 99%